Fontes de informação para acadêmicos do Programa de Pós-Graduação em Agronomia Tropical - (:unkn) unknown (Brasil, 2018)
Presents the databases and scientific journals available within the specific knowledge area. It aims to show scholars where they can possibly find information to solve their information problems for the development of their respective research.
Information sources for academics of the Postgraduate Program Studies in Tropical Agronomy
Keywords: Base de dados; Fontes de informação; Informational sources; Tropical Agronomy; Informational databases; Journals; CIÊNCIAS AGRÁRIAS: AGRONOMIA